Biogenic synthesis, characterization, and evaluation of synthesized nanoparticles against the pathogenic fungus Alternaria solani - Narware, Jeetu; Singh, Satyendra P.; Manzar, Nazia; Kashyap, Abhijeet Shankar (Frontiers in Microbiology, 2023)
In the present study culture filtrate of Trichoderma harzianum was used as a reducing and capping agent for quick, simple, cost-effective, and eco-friendly synthesis of silver nanoparticle. The effect of different ratios (AgNO3: Culture filtrate), pH, and incubation time were also examined on the synthesis of silver nanoparticle. Distinctive surface plasmon resonance (SPR) peak at 420nm was seen in the UV-Vis spectra of synthesized silver nanoparticles. Spherical-shaped and monodispersed nanoparticles were observed using scanning electron microscopy (SEM). The existence of elemental silver was confirmed by the peak in the silver area shown by energy dispersive X-ray spectroscopy (EDX).Crystalline nature of silver nanoparticles confirmed by X-ray diffraction (XRD), Fourier trans-infrared (FTIR) was used to examine the functional groups present in culture filtrate. Dynamic light scattering (DLS) revealed the average size (43.68 nm) and reported to be stable for four months. Atomic force microscopy (AFM) was used to confirm the surface morphology. We also investigated the in-vitro antifungal efficacy of biosynthesized AgNPs against Alternaria solani, which demonstrated the significant inhibitory effect on mycelial growth and spore germination. Additionally, the microscopic investigation revealed that AgNPs treated mycelia exhibited defects and collapsed. Other than this, AgNPs was also tested in an epiphytic environment against Alternaria solani. AgNPs were shown to be capable of managing the early blight disease based on the findings of the field trial. The maximum percentage of inhibition of early blight disease by nanoparticles was observed at 40ppm (60.27%) followed by 20 ppm (58.68%) whereas in the case of fungicide mancozeb (1000ppm) inhibition was recorded 61.54%.